Anaplastic Large-Cell Lymphoma in a Child with Type I Diabetes and Unrecognised Coeliac Disease - Jemima Sharp; Barry Pizer; George Kokai; Marcus K. H. Auth (Hindawi Limited, 2012)
Screening for coeliac disease is recommended for children from certain risk groups, with implications for diagnostic procedures and dietetic management. The risk of a malignant complication in untreated coeliac disease is not considered high in children. We present the case of a girl with type I diabetes who developed weight loss, fatigue, and inguinal lymphadenopathy. Four years before, when she was asymptomatic, a screening coeliac tTG test was positive, but gluten was not eliminated from her diet. Based on clinical examination, a duodenal biopsy, and an inguinal lymph node biopsy were performed, which confirmed both coeliac disease and an anaplastic large-cell lymphoma. HLA-typing demonstrated that she was homozygous for HLA-DQ8, which is associated with higher risk for celiac disease, more severe gluten sensitivity, and diabetes susceptibility. She responded well to chemotherapy and has been in remission for over 4 years. She remains on a gluten-free diet. This is the first case reporting the association of coeliac disease, type I diabetes, and anaplastic large-cell lymphoma in childhood. The case highlights the malignancy risk in a genetically predisposed individual, and the possible role of a perpetuated immunologic response by prolonged gluten exposure.